Comparative Study of Physiochemical Properties and Microbial Population in Forest and Shifting Cultivation Soil in Mizoram, India - Mawblei, Backson; Sahoo, Uttam Kumar; Musa, Faisal Ismail; Ramtharmawi, Ramtharmawi (Talenta Publisher, 2025)
Forest loss due to shifting cultivation (jhum) is believed to have intensified in recent years, primarily due to increasing population pressures and shorter fallow cycles. This study aims to examine the physiochemical properties and microbial population in forest soil and soil under shifting cultivation (jhum) in Mizoram, India. Soil samples were collected randomly in forest and shifting area using three depths (0 – 15 cm, 16 – 30 cm and 31 – 45 cm). Forest soil exhibited higher nitrogen (N) level, organic carbon content, moisture content and microbial diversity compared to shifting cultivation soil, which showed slightly higher phosphorus (P) level and comparable potassium (K) concentrations. Correlation revealed that forest soil had lower bulk density and higher water-holding capacity, linked to their enhanced organic matter and microbial activity. Additionally, shifting cultivation was associated with soil compaction, reduced nutrient availability and lower microbial populations, highlighting the negative impact of land-use change on soil health and ecosystem functioning. Moreover, these findings emphasize the need for sustainable land management practices to mitigate soil degradation and support soil fertility in shifting cultivation system